Administration of gallus domesticus boiled chicken white egg increased amh levels of premenopausal female wistar rats - Liya Rosdiana; Wimpie Pangkahila; I Gusti Made Aman (Fakultas Kedokteran Universitas Udayana, 2019)
Introduction: Aging is a complex multifactorial process and leads to functional changes one of which is the decline in reproductive function. Decrease in reproductive function in women in in the form of decreased ovarian reserve can be detected by low levels of Anti_mullerian Hormone (AMH). This study aims to prove the effect of administration of Gallus domesticus boiled chicken white egg increased AMH levels of premenopausal female wistar rats. Methods: This research was experimental animal with Pretest-Posttest Control Group Design. The study conducted on 16 premenopausal female wistar mices, aged 17-18 months, weighing 250-260 grams. The mice were divided into 2 goups: the control group (placebo), which was given gelatin flour by 7.3 gram 3 times daily for 4 weeks and the group treted with Gallus domesticus boiled chicken white egg by 7.3 gram 3 times daily for 4 weeks by oral. Blood AMH level were measured before and after treatment for both group. Results: The result showed that before treatment, mean AMH level both in control group and treatment group were not significantly different (p > 0,05). After treatment, mean AMH level both in control group and treatment group were significantly different (p < 0,05). The administration of Gallus domesticus boiled chicken white egg increased AMH levels by 0.804 ng/ml. Conclusion: It can be concluded that administration of Gallus domesticus boiled chicken white egg increased AMH level. The mean AMH level after treatment had a significant difference between control group (placebo) and treatment group with p = 0.001.